Acute effects of different warm-up methods on sprint, slalom dribbling, and penalty kick performance in soccer players - Gelen, E. (The Journal of Strength and Conditioning Research, 2010)
Although pre-event static stretching is an accepted practice in most athletics program, pre-event dynamic exercise is becoming popular. The purpose of this study was to compare the acute effects of different warm-up methods on soccer performance. Twenty-six professional soccer players (23.3 +/- 3.2 years, 178.2 +/- 6.1 cm, and 73.0 +/- 6.5 kg) performed 4 different warm-up routines in random order on nonconsecutive days. The warm-up methods consisted of only 5 minutes of jogging (Method A), 5 minutes of jogging and static stretching (Method B), 5 minutes of jogging and dynamic exercise (Method C), and 5 minutes of jogging and a combination of static stretching and dynamic exercise (Method D). After each warm-up session, subjects were tested on the sprint, slalom dribbling, and penalty kick performance. Methods A-D were compared by repeated-measures analyses of variance and post hoc comparisons. In this study, existence of a significant drop in sprint, slalom dribbling, and penalty kick performances of Method C has been determined in comparison with that of Method A (p < 0.05). Again for sprint, slalom dribbling, and penalty kick performances of Method A in comparison with those of Method A, the existence of a significant increase has been determined (p < 0.05). In Method D in comparison with Method A, for sprint, slalom dribbling, and penalty kick performances, existence of no significant difference has been determined (p > 0.05). The results of this study suggest that it may be desirable for soccer players to perform dynamic exercises before the performance of activities that require a high power output.